Steering an adaptive antenna array by LMS algorithm - Gargouri, L.; Ghayoula, R.; Fadlallah, N.; Gharsallah, A.; Rammal, M. (2009 16th IEEE International Conference on Electronics, Circuits, and Systems, 2009)
An adaptive antenna system consists of a combination of multiple antenna elements with a signal-processing capability to optimize its radiation and/or reception pattern automatically in response to the signal environment. In a telecommunication system, adaptive antenna system is the port through which radio frequency (RF) energy is coupled from the transmitter to the environment and, in reverse, to the receiver from the environment. In this paper, an efficient method for the pattern synthesis of the linear antenna arrays with the prescribed nulling and steering lobe is presented. The proposed method is based on LMS algorithm. This paper proposes the novel architecture for implementing a least mean square (LMS) algorithm, using an 8 quasi-Yagi array with its feeding system.